Prevalence of gonorrhea among adult male with urethritis in Erbil City - Mansoor, Isam Yousif (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Gonorrhea is a sexually transmitted disease caused by Neisseria gonorrhoeae. The bacteria can be passed from one person to another through vaginal, oral, or anal sex. It can also be passed from mother to her baby during birth. The symptoms in adult male include a burning sensation when they urinate and a yellowish-white discharge may ooze out of the urethra. Gonorrhea can spread to epididymis causing pain and swelling in the testicular area. This can create scar tissue that can lead to infertility. The aim of this study was to determine the prevalence of gonorrhea in adult male in Erbil Governorate and the susceptibility of isolated Neisseria to antibiotics. Methods: Urethral discharge obtained from adult male aged between 19-49 years were examined for the presence of Neisseria gonorrhoeae using direct smear gram staining and cultural technique. The susceptibility of isolated bacteria to antibiotics was tested using disc diffusion method. Results: This study showed that the incidence of gonorrhea among 312 adult male with urethritis in Erbil city was (8.97%) while (91.03%) of patients examined had nongonococcal urethritis. The higher percentage of infection with Neisseria gonorrhoeae (14%) occurred among age group (19-29) years and the lower (3.48%) in the age group (39-49) years. Among the 210 unmarried patients, 26 (12.38%) had gonorrhea and 184 (87.62%) had nongonococcal urethrits. All Neisseria gonorrhoeae were sensitive to ceftriaxone, spectinomycin and azithromycin. The isolates showed low sensitivity (21.42%) to penicillin. Conclusion: It seems that gonorrhea is common among symptomatic adult male. The emergence of resistance to some antibiotics is worrying. Appropriate prevention strategies should be of highest priority of the policy makers.